بناء برنامج تعليمي قائم على الوسائط المتعددة في تعلم مفردات اللغة العربية وتعليمها عبر برنامج ”موودل“ في ضوء احتياجات الطلبة في الجامعة الإسلامية العالمية بماليزيا = The design of a multimedia program for teaching and learning Arabic vocabulary via an Moodle platform, in perspective of the students’ needs at International Islamic University in Malaysia - Zainuddin, Nurkhamimi; Sahrir, Muhammad Sabri (Al-Quds Open University, 2017)
This study attempts to analyze needs and principles for the design and development of multimedia program for teaching and learning Arabic vocabulary via an application named Moodle. The researchers talked about the tools, samples and steps which are related to the design and development process. This study used “Needs Analysis Questionnaire” in conducting the research method. 100 students and two lecturers from the Center for Foundation Studies were among the study population. International Islamic University in Malaysia had participated in the study which was carried out during the second semester of 2013/ 2014 academic year. The authors employed the results of these needs analysis in the development of multimedia program for teaching and learning Arabic vocabulary via Moodle and learned through the Moodle.